MEDIA KURIKULUM GAMBAR BERWARNA DALAM MENINGKATKAN KEMAMPUAN ANAK USIA DINI MENGENAL HURUF HIJAIYAH - Nuraisyah, Nuraisyah (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
he mental Mental health issues faced by Gen Z are becoming increasingly complex due to rapid technological advances and socio-cultural changes. Social pressure from social media, unrealistic self-comparison, academic stress, demands for success, and excessive use of social media can worsen Gen Z's mental health. Psychological support and holistic education are needed to overcome these challenges. Islamic education concept from Buya Hamka's perspective can be an alternative in dealing with the mental health crisis in Gen Z. This study aims to explain Islamic education from Buya Hamka's perspective and its relevance to strengthening Gen Z's mental health, especially through the application of the values of aqidah, morality, and balance between reason and soul. This study uses a library research method.The results of the study revealed that Buya Hamka's Islamic educational concept emphasizes the importance of aqidah, akhlaq, and balance between reason and soul in strengthening Gen